2004
DOI: 10.1124/jpet.104.065268
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant Activity of Progesterone and Neurosteroids in Progesterone Receptor Knockout Mice

Abstract: Many of the biological actions of progesterone are mediated through the progesterone receptor (PR), a nuclear transcription factor. Progesterone is well recognized to protect against seizures in animal models. Although this activity has been attributed to the progesterone metabolite allopregnanolone, a GABA A receptor-modulating neurosteroid with anticonvulsant properties, PRs could also play a role. Here, we used PR knockout (PRKO Ϫ/Ϫ ) mice bearing a targeted deletion of the PR gene that eliminates both isof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
177
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(184 citation statements)
references
References 51 publications
5
177
0
2
Order By: Relevance
“…Moreover, a single subcutaneous injection of progesterone mimicked the effect of incubating the spinal cord slices with precursors of AP, suggesting that peripheral fluctuations in steroid or steroid precursor levels might affect the production of neurosteroids in the spinal cord. Similar observations have been made in other areas of the CNS after peripheral injections of steroids (Reddy et al, 2004(Reddy et al, , 2005 or after endogenous fluctuations of steroid levels associated with ovarian cycle (Maguire and Mody, 2007) or stress (Reddy and Rogawski, 2002).…”
Section: Discussionsupporting
confidence: 64%
“…Moreover, a single subcutaneous injection of progesterone mimicked the effect of incubating the spinal cord slices with precursors of AP, suggesting that peripheral fluctuations in steroid or steroid precursor levels might affect the production of neurosteroids in the spinal cord. Similar observations have been made in other areas of the CNS after peripheral injections of steroids (Reddy et al, 2004(Reddy et al, , 2005 or after endogenous fluctuations of steroid levels associated with ovarian cycle (Maguire and Mody, 2007) or stress (Reddy and Rogawski, 2002).…”
Section: Discussionsupporting
confidence: 64%
“…3α-Androstanediol is structurally similar to allopregnanolone and conferred seizure protection in the 6-Hz electroshock model of epilepsy (Kaminski et al, 2004). Overall, the anticonvulsant profile of 3α-androstanediol is highly consistent with other GABA A receptor modulating neurosteroids including allopregnanolone and THDOC, which have similar spectrum of anticonvulsant activity in animal seizure models (Belelli et al, 1989;Kokate et al, 1994;Reddy and Rogawski, 2002;Reddy et al, 2004;Reddy, 2006).…”
Section: Anticonvulsant Activity Of 3α-androstanediolmentioning
confidence: 52%
“…It is suggested that the sex differences could be due to steroid hormones or sexually dimorphic characteristics in specific brain areas relevant to epilepsy (Cooke et al, 1999;Reddy, 2003b;Ravizza et al, 2003). Current experimental evidence indicates that progesterone-and testosterone-derived neurosteroids could be involved in sexual dimorphism in neural excitability and seizure susceptibility (Cooke et al, 1999;Reddy et al, 2004;Reddy, 2006). The progesterone-derived neurosteroid allopregnanolone is a powerful GABA A receptor-modulating neurosteroid with anticonvulsant properties (Reddy et al, 2001;.…”
Section: Gender-related Seizure Susceptibilitymentioning
confidence: 99%
“…Endogenous neurosteroids are potent allosteric agonists of GABA-A receptors. Allopregnanolone (3-hydroxy-5-pregnan-20-one, AP) is an endogenous neurosteroid with potent antiseizure effects mediated by GABA-A receptors (Reddy et al, 2014;Clossen and Reddy, 2017a). Neurosteroids have a greater sensitivity for GABA-A receptors, which are highly expressed in the dentate gyrus (Brown et al, 2002;Bianchi and Macdonald, 2003;Carver and Reddy, 2013;.…”
Section: Introductionmentioning
confidence: 99%